Ecoriparian Feasibility Study in Pekanbaru, Riau : Ecoriparian Feasibility Study in Pekanbaru, Riau - Sukma Laksita Rahma; Annastasia Ayu Arcitra; Tjahjo Tri Hatono; Akhmad Arifin Hadi (Universitas Ibn Khaldun Bogor, 2023)
The total pollution load reduction in 2021 has been achieved by 75.57 tons of BOD per year. The total accumulated reduction in waste water pollution load from 2015 to 2021 is 186.68 metric tons/BOD/year. We want to obtain ecoriparian locations to be used as a reference for ecoriparian development as a form of technical regulations compensation. Data analysis techniques using a descriptive statistical method, wherein the weighting of each aspect indicator is multiplied and the sum becomes a relative value for determining the feasibility of an ecoriparian location. In determining ecoriparian locations, there are criteria that cover ecological aspects, economic aspects, social aspects, technical aspects, and institutional aspects.Based on the results of determining the location options, the highest feasibility value for the study location was obtained, namely Muhammadiyah Riau University (UMRI). However, even though the total score at the UMRI location received the highest score, this location is still not suitable as an eco-district location.The results of the feasibility of ecoriparian locations are based on five important aspects. These important aspects are ecological aspects, economic aspects, social aspects, technical aspects, and institutional aspects. Based on the results of determining the location of these three location options, namely Kampung Bandar, Ex-Rubber Factory, and Muhammadiyah Riau University (UMRI), the highest study location feasibility score was obtained.